The Relationship between Learning Climate and Learning Interest of Package B Equality Students in PKBM Sentosa Hati - Bismi Nurvallah; MHD Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research was motivated by the low interest in learning for the residents of learning package B at PKBM Sentosa Hati, Padang City. Researchers suspect that one of the contributing factors is an unfavorable learning climate. This study aims to (1). To describe the learning climate, (2). To describe interest in learning, (3). Seeing the relationship between the learning climate and the learning interest of the residents studying Package B at PKBM Sentosa Hati, Padang City. This research is a type of correlation research using a quantitative approach. The population of this study is the study residents, totaling 35 people. And sampling with simple random sampling technique. The data collection technique used a questionnaire and the data analysis technique used the percentage formula and rank order. The results showed that the learning climate of residents studying Package B at PKBM Sentosa Hati, Padang City was not very supportive. The learning interest of learning residents is low. And there is a significant relationship between the learning climate and the learning interest of the residents in learning package B at PKBM Sentosa Hati, Padang City. It is suggested to administrators oreducators at PKBM Sentosa Hati, Padang City to pay attention to the learning climate because this affects the learning interest of learning citizens. The better the learning climate applied, the higher the learning interest of students. On the other hand, a learning climate that is not good will affect the learning interest of learningcitizens.Keywords: learning climate, interest in learning, package B